A study on the correlation between high performing school (HPS) attributes and teacher`s attitudes in selected schools. / Olivia Inang and Sainti John - Inang, Olivia; John, Sainti (2014)
The researchers seen the fact that only two schools had been recognized as High Performing School (HPS) in Sabah and it triggered them to conduct the study. The study examines the correlation between the attributes of HPS and the teacher’s attitude. A set of 140 questionaires had been distributed to four schools. The school that have been chosen by the researchers are SK. Kolombong Kota Kinabalu, SRK. Lok Yuk Inanam, SRK. Sacred Heart Kota Kinabalu and SK. St. Francis Convent (M) Kota Kinabalu. The study reveals that there is a moderate correlation between the teacher’s perception towards the attributes of HPS and the teacher’s attitude